Comparison of ixekizumab with ustekinumab in moderate‐to‐severe psoriasis: 24‐week results from IXORA‐S, a phase III study. (19th July 2017) - Reich, K.; Pinter, A.; Lacour, J.P.; Ferrandiz, C.; Micali, G.; French, L.E.; Lomaga, M.; Dutronc, Y.; Henneges, C.; Wilhelm, S.; Hartz, S.; Paul, C.; et al.
Summary: Background: It has been shown that the interleukin (IL)‐23/IL‐17 axis is critical in the pathogenesis of psoriasis. Objectives: To present the primary end point (week 12) and safety and efficacy data up to week 24 from a head‐to‐head trial (IXORA‐S) of the IL‐17A inhibitor ixekizumab (IXE) vs. the IL‐12/23 inhibitor ustekinumab (UST). Methods: Randomized patients received IXE (160‐mg starting dose, then 80 mg every 2 weeks for 12 weeks, then 80 mg every 4 weeks, n = 136) or UST (45 mg or 90 mg weight‐based dosing per label, n = 166). The primary end point was the proportion of patients reaching ≥ 90% Psoriasis Area and Severity Index improvement (PASI 90). Hommel‐adjusted key secondary end points at week 12 included PASI 75, PASI 100, static Physician's Global Assessment (sPGA) score of 0 or 1, sPGA score of 0, Dermatology Life Quality Index (DLQI) score of 0 or 1, ≥ 4‐point reduction on the itch numerical rating scale (NRS) and changes in itch NRS and skin pain visual analogue scale. Results: At week 12, IXE ( n = 99, 72·8%) was superior to UST ( n = 70, 42·2%) in PASI 90 response (response difference 32·1%, 97·5% confidence interval 19·8−44·5%, P < 0·001). Response rates for PASI 75, PASI 100 and sPGA (0, 1) were significantly higher for IXE than for UST (adjusted P < 0·05). At week 24, IXE‐treated patients had significantly higher response rates than UST‐treated patients for PASI, sPGA and DLQI (unadjusted P < 0·05). No deaths were reported, and the treatments did not differ with regard to overall incidences of adverse events ( P = 0·299). Conclusions: The superior efficacy of IXE demonstrated at week 12 persisted up to week 24. The safety profiles were consistent with those previously reported for both treatments. Abstract : What's already known about this topic? With the advancements in new biologics targeting the interleukin (IL)‐17A pathway, the majority of patients with moderate‐to‐severe psoriasis are now able to achieve complete or near complete clearance of psoriasis. What does this study add? The IL‐17A inhibitor ixekizumab provides superior efficacy over the IL‐12/23 inhibitor ustekinumab, with a similar safety profile after 24 weeks of treatment. Linked Comment:Chu et al . Br J Dermatol 2017; 177:896–897 .